2022
DOI: 10.1101/2022.04.03.22273355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Variables Correlate with Serum Neutralizing Antibody Titers after COVID-19 mRNA Vaccination in an Adult, US-based Population

Abstract: Background: We studied whether comorbid conditions impact strength and duration of immune responses after SARS-CoV-2 mRNA vaccination in a US-based, adult population. Methods: Sera (pre-and-post-BNT162b2 vaccination) were tested serially up to 6 months after two doses of vaccine for SARS-CoV-2-anti-Spike neutralizing capacity by pseudotyping assay in 91 Veterans and 33 healthcare workers; neutralizing titers were correlated to clinical variables with multivariate regression. In 36 participants, post-booste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Among older male residents, those with CVD were more likely to have a lower antibodies response compared to CVD-free participants. As far as CVD are concerned, previous studies provide results similar to ours since antibody titers were found to be decreased in individuals with chronic heart disease or those with more severe congenital cardiopathies [ 23 , 24 ]. Conversely, another work did not see any apparent difference in response to influenza vaccination between patients with coronary artery diseases and controls [ 25 ].…”
Section: Discussionsupporting
confidence: 84%
“…Among older male residents, those with CVD were more likely to have a lower antibodies response compared to CVD-free participants. As far as CVD are concerned, previous studies provide results similar to ours since antibody titers were found to be decreased in individuals with chronic heart disease or those with more severe congenital cardiopathies [ 23 , 24 ]. Conversely, another work did not see any apparent difference in response to influenza vaccination between patients with coronary artery diseases and controls [ 25 ].…”
Section: Discussionsupporting
confidence: 84%
“…Similar changes in S‐IgA were observed: 8‐fold decrease at T1/T2, 9‐fold increase at T3 compared to T2, comparable to mean T1 values. Zhao et al 37 also found a decrease of neutralizing antibodies at month 6 compared to their values at the 1st month after the second dose of mRNA vaccines, but an increase at 1 and 3 months postbooster. A decrease of anti‐S‐RBD antibody titers over time after the second dose and approximately 14‐fold increase after the booster dose compared to levels after the second dose was also reported.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, a positive correlation was found between eGFR and anti‐spike Ab in subjects with diabetes; this evidence is supported by the same findings of the COVAC‐DM study. 15 Indeed, a reduction in kidney function could be related to the reduced efficacy of the SARS‐CoV‐2 vaccine, 21 , 22 but the same was also observed for other vaccination. 23 Considering that the presence of chronic kidney disease is also associated with hospitalisation for Covid‐19 in subjects with DM2, 24 further studies are needed to evaluate the efficacy of SARS‐CoV‐2 vaccination in people with impaired kidney function.…”
Section: Discussionmentioning
confidence: 71%